Know your neighbors: microbial recognition at the intestinal barrier and its implications for gut homeostasis and inflammatory bowel disease - Iyer, Krishna; Erkert, Lena; Becker, Christoph (Frontiers in Cell and Developmental Biology, 2023)
Intestinal epithelial cells (IECs) perform several physiological and metabolic functions at the epithelial barrier. IECs also play an important role in defining the overall immune functions at the mucosal region. Pattern recognition receptors (PRRs) on the cell surface and in other cellular compartments enable them to sense the presence of microbes and microbial products in the intestinal lumen. IECs are thus at the crossroads of mediating a bidirectional interaction between the microbial population and the immune cells present at the intestinal mucosa. This communication between the microbial population, the IECs and the underlying immune cells has a profound impact on the overall health of the host. In this review, we focus on the various PRRs present in different cellular compartments of IECs and discuss the recent developments in the understanding of their role in microbial recognition. Microbial recognition and signaling at the epithelial barrier have implications in the maintenance of intestinal homeostasis, epithelial barrier function, maintenance of commensals, and the overall tolerogenic function of PRRs in the gut mucosa. We also highlight the role of an aberrant microbial sensing at the epithelial barrier in the pathogenesis of inflammatory bowel disease (IBD) and the development of colorectal cancer.